Early Versus Late Immunomodulatory Therapy in Vogt-Koyanagi-Harada disease - Philip, P. Storey; Jeffrey, J. Tan; Hassan, A. Aziz; On-Tat, Lee; Jiun, Do; Brandon, Wong; Anna, Ter-Zakarian; Damien, C. Rodger; Narsing, A. Rao (Journal of Ophthalmic Science, 2017)
Purpose: To evaluate early versus late immunomodulatory therapy (IMT) for patients following initial diagnosis of Vogt-Koyanagi-Harada (VKH) disease. Methods: Retrospective review including all VKH patients seen 5/1/2014 to 4/1/2016 at LAC+USC. Early IMT was defined as starting an immunomodulatory agent within 3 months of corticosteroid initiation. Results: Twenty-seven patients were included, of whom 15 received early IMT and 8 received late IMT. Early IMT patients trended toward greater improvement in vision compared to late IMT (logMAR 0.59 vs. 0.11; p=0.14) with no differences in ocular complications including ocular hypertension (p=0.53) and cataract (p=1.0). Patients receiving early IMT averaged 0.93 recurrences versus 2.13 recurrences for late IMT (p=0.092). Of patients successfully taper off oral corticosteroids, the early IMT group was tapered in an average of 8.3 months versus 19.8 months for late IMT (p=0.0019). Conclusions: Early IMT in VKH may allow for shorter duration of corticosteroids with similar visual outcomes, ocular complications, and disease recurrences.
Keywords: complications; immunomodulatory therapy; Vogt-Koyanagi-Harada disease